2015
DOI: 10.4103/0976-9668.159988
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the diagnosis and treatment of childhood tuberculosis

Abstract: Despite over 2.3 million (26% of global burden) cases of tuberculosis (TB) in India the accurate diagnosis of childhood TB remains a major challenge. Children with TB usually have paucibacillary disease and contribute little to disease transmission within the community. Consequently the treatment of children with TB is often not considered a priority by TB control programmes. Adequate and timely assessment of TB infection in childhood could diminish epidemiological burden as underdiagnosed pediatric patients c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
0
27
0
5
Order By: Relevance
“…Children with TB are often not diagnosed and reported because of limited capacity of frontline health providers [4,5], lack of dedicated child health services with experienced and appropriately trained clinicians [4], non-specific symptoms overlapping with other common childhood diseases [6], complex diagnostic algorithms [6,7], lack of a sensitive point of care test and technical resources [8], and minimal contact tracing activities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Children with TB are often not diagnosed and reported because of limited capacity of frontline health providers [4,5], lack of dedicated child health services with experienced and appropriately trained clinicians [4], non-specific symptoms overlapping with other common childhood diseases [6], complex diagnostic algorithms [6,7], lack of a sensitive point of care test and technical resources [8], and minimal contact tracing activities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, diagnosis of TB in children is challenging due to its nonspecific clinical presentation and its paucibacillary nature as well as the frequent extrapulmonary localization of the disease. Current pediatric guidelines recommend applying a combination of clinical, radiological, microbiological, and immunological approaches to improve the diagnostic yield (2)(3)(4).…”
mentioning
confidence: 99%
“…This study indicated that diagnosis of childhood TB by private providers was mainly based on clinical features, radiography and microscopy, rarely tuberculin skin tests, histopathology and Gene-Xpert MTB/RIF. Other settings also show that TB diagnosis in children is often based on a combination of clinical symptoms and chest X-ray; this could be due to the lack of a simple and precise diagnostic tool especially at the peripheral level, or due to inadequate training and capacity of health care workers [13][14][15][16][17][18][19]. However, in Pakistan, the availability of diagnostic tools varies across the country, where chest X-ray and smear microscopy are almost universally available and used for TB diagnosis at peripheral level.…”
Section: Discussionmentioning
confidence: 99%